Beyond pleasure and pain how motivation works - Higgins, E. Tory (Edward Tory), 1946- (New York : Oxford University Press, 2012)
How does motivation work? Scientific research shows that people are motivated by more than the pursuit of pleasure and the avoidance of pain. Higgins argues that people are motivated by the pursuit of value, truth, and control, but the central story to motivation lies in how these elements work together.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 19, 2012).
Includes bibliographical references and index.
Keywords: Motivation (Psychology)